The Effect of Environmental Performance Innovation: The Strategic Role of Institutional Ownership as a Moderator - Panggabean, Angelita Kracibaya Nauli; Suhartini, Dwi (JIEMAN: Journal of Islamic Educational Management, 2025)
This study aims to examine the impact of environmental performance on innovation and analyze the role of institutional ownership as a moderating variable. The increasingly critical issue of sustainability has prompted, especially in the manufacturing sector, the adoption of environmentally friendly practices that are believed to encourage innovation. However, the relationship between environmental performance and innovation still shows mixed results. This study employs a quantitative approach using Partial Least Squares-Structural Equation Modeling analysis on 150 observational data points from 30 manufacturing companies listed on the Indonesia Stock Exchange and participating in the PROPER program during the 2019-2023 period. The research findings indicate that environmental performance has a significant negative effect on corporate innovation. However, institutional ownership has been proven to positively and significantly moderate this relationship. These findings confirm that the presence of strong institutional investors can act as a catalyst in driving innovation amid environmental performance demands. This study has implications for policymakers and investors that proper ownership governance can create a balance between sustainability and corporate innovation in developing countries